Price and Location on Patient Treatment Decisions Outpatient Care in General Practitioner Practices - Marhanifah, Attinna; Santoso, Ariadi; Yunanto, Yogi (JEM17: Jurnal Ekonomi Manajemen, 2024)
This study aims to determine the influence of Price and Location on the decision of outpatient treatment patients at Doctor Niko General Practice Jl. Tengger Surabaya. The influence you want to know is both direct and indirect. This type of research uses a quantitative approach. This study used a sample of 100 respondents. Sampling using nonprobabilty sampling technique with purposive sampling method. The test tool used was Data analysis using SPSS 25, in this study using questionnaires or questionnaires and the analysis used was multiple linear regression. From the results of this test, it can be concluded that partially, Price (X1) and Location (X2) have a positive and significant effect on the decision of outpatient patients at Doctor Niko General Practice Jl. Tengger Surabaya. Price (X1) and Location (X2) simultaneously have a positive and significant influence on the decision of outpatient treatment at Doctor Niko General Practice Jl. Tengger Surabaya. The Location Variable (X2) is more dominant in influencing the decision of outpatient patients at the General Practice of Doctor Niko Jl. Tengger Surabaya than the Price Variable. Keywords: Location, Price, Treatment Decision.